A rapid and universal liquid chromatograph-mass spectrometry-based platform, refmAb-Q nSMOL, for monitoring monoclonal antibody therapeutics. Issue 19 (23rd August 2022) - Iwamoto, Noriko; Koguchi, Yoshinobu; Yokoyama, Kotoko; Hamada, Akinobu; Yonezawa, Atsushi; Piening, Brian D.; Tran, Eric; Fox, Bernard A.; Redmond, William L.; Shimada, Takashi
Abstract : Accurate multiplexed quantitation of unique signature peptides derived from monoclonal antibody therapeutics with a universal reference antibody refmAb-Q using Fab-selective proteolysis nSMOL coupled with LC-MS/MS. Abstract : Accurate quantitation of antibodies is critical for development of monoclonal antibody therapeutics (mAbs). Therapeutic drug monitoring has been applied to measure levels of mAbs in clinics for dose adjustment for autoimmune disease. Trough levels of mAbs can be a biomarker for cancer immunotherapy. Thus, the deployment of a rapid and universal platform for mAb monitoring may benefit processes ranging from drug development to clinical practice for a wide spectrum of diseases. However, mAb monitoring often requires development and conduct of an individual ligand binding assay such as ELISA, which is impractical to scale. We streamlined quantitation of antibody therapeutics by a nano-surface and molecular-orientation limited (nSMOL) proteolysis assay using LC-MS with a universal reference antibody (refmAb-Q), for accurate multiplexed quantitation of unique signature peptides derived from mAbs. This innovative refmAb-Q nSMOL platform may provide a practical solution for quantitating an ever-increasing number of mAbs from developmental to clinical use settings.